Expression and characterization of a novel mesophilic protease from metagenomic library derived from Antarctic coastal sediment - Zhang, Yingjing; Zhao, Jing; Zeng, Runying; 赵晶 (EXTREMOPHILES, 2011)
National High Technology Research and Development Program (863 program) [2007AA091407]; China Ocean Mineral Resources R&D Association (COMRA) [DYXM-115-02-2-04] A metagenomic cosmid library was constructed, in which the insert DNA was derived from the coastal sediment near Antarctic China Zhongshan Station. One clone (ACPRO001) expressing protease activity was isolated from the library using milk agar plates. Sequencing of the clone revealed a novel protease gene. The amino acid sequence comparison and phylogenetic analysis indicated that it could be classified as a subtilisin-like serine protease, though the highly conserved residue Asp was replaced by Ala. The ACPRO001 protease gene was expressed in pET-His and purified for characterization. The optimal temperature and pH for the activity of the ACPRO001 protease were 60A degrees C and pH 9.0, respectively. The enzyme retained about 73% of residual activity after 2 h incubation at 50A degrees C in the presence of Ca(2+). The presence of Ca(2+) increased the thermostability of ACPRO001 protease obviously. The enzymatic activity was inhibited by 1 mM phenylmethyl sulfonylfluoride (PMSF) and hydrochloride 4-(2-aminoethyl)-benzenesulfonyl fluoride (AEBSF), indicating that it was a serine protease.